2021
DOI: 10.3390/gels7030091
|View full text |Cite
|
Sign up to set email alerts
|

Softness, Elasticity, and Toughness of Polymer Networks with Slide-Ring Cross-Links

Abstract: Slide-ring (SR) gels cross-linked by ring molecules are characterized by softness (low Young’s modulus), elasticity (low hysteresis loss), and toughness (large fracture energy). In this article, the mechanical and fracture properties of SR gels are reviewed to clarify the physical understanding of the relationship between the molecular-level sliding dynamics of the slide-ring cross-links and macroscopic properties of SR gels. The low Young’s modulus and large fracture energy of SR gels are expressed by simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…The incorporation of sliding cross-links into polymer networks has been demonstrated as an interesting strategy to achieve high stretchability and mechanical elasticity, in addition to promoting self-healing. For example, the introduction of polyrotaxanes (PRs) constitutes a representative method in the development of slidable polymer networks . PRs are necklace-like supramolecules in which cyclodextrins (CDs) are threaded onto linear polymer chains that are capped with bulky end groups.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of sliding cross-links into polymer networks has been demonstrated as an interesting strategy to achieve high stretchability and mechanical elasticity, in addition to promoting self-healing. For example, the introduction of polyrotaxanes (PRs) constitutes a representative method in the development of slidable polymer networks . PRs are necklace-like supramolecules in which cyclodextrins (CDs) are threaded onto linear polymer chains that are capped with bulky end groups.…”
Section: Introductionmentioning
confidence: 99%
“…In SR gel models, the axis chains are covered by cyclic molecules. Each cyclic molecule comprises eight beads, whose inner diameter was sufficiently large to slide freely on an axis chain. , Mayumi et al reported that the crack propagation resistance was dependent on the slidable range for cross-links, which is dominated by the number of axis chain monomers, instead of the cross-link density. , Thus, we set the same number of cross-links for SR gels with various coverages to ensure that the number of axis chain monomers per cross-links is the same to clarify the effect of coverage on the mechanical properties at the same slidable range for cross-links. We prepared various SR gels with different coverages by changing the number of cyclic molecules per axis chain, M .…”
Section: Methodsmentioning
confidence: 99%
“…The conformational change between ring and chain has a decisive effect on the mechanical properties of glide ring gel. Reducing the covering area of the ring and increasing the length of the shaft chain can improve the toughness [ 45 , 46 ]. Because of the existence of the ring-chain, the selection of monomer is also limited, and the influence of conformation change on mechanical properties leads to more complex mechanical behavior.…”
Section: Mechanical Reinforcement Methodsmentioning
confidence: 99%